Network Digital Education. Moving into the digital age - Henriques, S.; Henriques, Susana (ICUDDR Webinars, 2020)
We are all facing unprecedented changes as we are moving into a digital age and need to move from a transmission model of education (‘instruction’) to the facilitation of learning (‘teaching’). In this webinar I will approach the following topics: • What strategies work best when teaching in a technology-rich environment? – different models • How is communication and interaction in digital network education scenarios; • Pedagogical design – e-activities and e-assessment • How to maintain high quality in teaching in a rapidly changing learning environment while managing workload?